2014
DOI: 10.1371/journal.pone.0094851
|View full text |Cite
|
Sign up to set email alerts
|

SNPs for Parentage Testing and Traceability in Globally Diverse Breeds of Sheep

Abstract: DNA-based parentage determination accelerates genetic improvement in sheep by increasing pedigree accuracy. Single nucleotide polymorphism (SNP) markers can be used for determining parentage and to provide unique molecular identifiers for tracing sheep products to their source. However, the utility of a particular “parentage SNP” varies by breed depending on its minor allele frequency (MAF) and its sequence context. Our aims were to identify parentage SNPs with exceptional qualities for use in globally diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 31 publications
2
84
0
5
Order By: Relevance
“…For example, Allen et al (2010) in a study on Irish cattle, reported a set of 43 SNPs for breed identification on the basis of allele frequency. Heaton et al (2014) identified 163 SNPs for use in parentage testing and traceability in sheep, using the minor allele frequency (>0.3). In Mastrangelo et al (2014), a subset of 119 SNPs was tested to evaluate their ability to assign individuals to the same groups that have been used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Allen et al (2010) in a study on Irish cattle, reported a set of 43 SNPs for breed identification on the basis of allele frequency. Heaton et al (2014) identified 163 SNPs for use in parentage testing and traceability in sheep, using the minor allele frequency (>0.3). In Mastrangelo et al (2014), a subset of 119 SNPs was tested to evaluate their ability to assign individuals to the same groups that have been used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of high throughput SNP platforms for livestock genomes has opened new perspectives for breed traceability. The BovineSNP50 and the OvineSNP50 BeadChip (Illumina, Inc., San Diego, CA), for example, have been widely used for investigating population genetic structures (Gautier et al, 2009), testing parentage (Heaton et al, 2014), studying selection signatures (Pintus et al, 2014;Kijas et al, 2012), and for calculating genomic breeding values . As a result, several thousands of animals of different breeds have been genotyped in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that DNA fingerprinting using MST markers could be cost effective for Australian Merino breeders if full pedigrees had been used in estimating EBVs by the BLUP procedure [3]. In addition, a review on recently common use of MST marker and SNP marker panels show affordability by researchers and farmers with future breeding perspectives [24,25,27,28,29]. However, SNPs, in terms of genetic information, are biallelic markers considered as a step backwards.…”
Section: Parameter Valuementioning
confidence: 99%
“…A typical microsatellite parentage test can be affordable for USD 25-35 per sheep. SNP of 100 markers tests, on the other hand, can be purchased for USD 15-20. Recently, for many reasons, SNPs have become the focus of efforts to improve sheep parentage testing [29]. However, SNP genotyping technologies are not available and affordable in each country and for each farmer.…”
Section: Parameter Valuementioning
confidence: 99%